Transfer printing of CVD graphene FETs on patterned substrates. Issue 33 (5th August 2015) - Abhilash, T. S.; De Alba, R.; Zhelev, N.; Craighead, H. G.; Parpia, J. M.
Abstract : Scalable fabrication of CVD graphene FETs on pre-patterned substrates. Abstract : We describe a simple and scalable method for the transfer of CVD graphene for the fabrication of field effect transistors. This is a dry process that uses a modified RCA-cleaning step to improve the surface quality. In contrast to conventional fabrication routes where lithographic steps are performed after the transfer, here graphene is transferred to a pre-patterned substrate. The resulting FET devices display nearly zero Dirac voltage, and the contact resistance between the graphene and metal contacts is on the order of 910 ± 340 Ω μm. This approach enables formation of conducting graphene channel lengths up to one millimeter. The resist-free transfer process provides a clean graphene surface that is promising for use in high sensitivity graphene FET biosensors.